Misprice, Leverage and Stock Buyback: Evidence in Indonesia - Lailiyah, Elliv Hidayatul; Purwanti, Ika; Sulton, Muhammad (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2020)
Cash distribution by stock buyback is one ways to increase stockholder wealth. This study is to analyze the effect of misprice (misvaluation) and leverage on stock buyback. Limited prior study discussed about stock buyback and misprice especially in Indonesia, theoritically, in Indonesia not only firm with undervalue stock do stock buyback but also firm with overvalue stock. Stock buyback can increase the stock prices, but the implementation in Indonesia is still small. Non-financial firms listed on the Indonesia Stock Exchange from 2010 to 2017 used in this study. Samples were taken by a purposive sampling method based on certain criteria. The data analysis techniques use multiple linear regression statistical analysis. The results showed that misprice has a positive effect on buyback. The different thing found in Indonesia because overvalued firms hold stock buyback. Leverage has a negative effect on stock buyback. Firms with leverage below the target tend to do a stock buyback. In addition, the stock buyback also used to correct prices (for undervalued stock to be fair). The implication in this study is stock buyback not only viewing to correct prices but also giving a signal to the market that the firm is in a good fundamental condition.